Incorporating Islamic Stories in Narrative Text Teaching Material for Islamic Boarding School Students - Saud, Indah Wardaty (Al-Lisan: Jurnal Bahasa, 2024)
Research focusing on incorporating religious values into language learning has recently grown, as reflected in the increasing number of related studies. As the world's largest Muslim-majority country, Indonesia has a crucial role in integrating Islamic values into education, particularly in the context of teaching English as a foreign language. This research aimed to develop an English module that contains Islamic values in narrative text material for students at MTs that is valid, practical, and effective. The Islamic values that have been integrated are prophetic stories and Islamic history which are very closely related to the environment of the Islamic boarding school for students at MTs Assalam and MTs Darul Istiqomah Manado. This research is a development research using the ADDIE model which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this research were 2 English teachers and 35 class IX students at MTs Assalam and Darul Istiqomah. Data collection techniques used included interviews, observation, and questionnaires. The material and media design experts have validated the module development with an average result of 90.5%, which means it is very valid. Furthermore, validation of users obtained data of 84.16% (very practical) from student users and 91% (very practical) from English teacher users. Therefore, it concluded that the English module containing Islamic values in Narrative text material meets practical criteria and can help teachers and students achieve learning goals.